Playing the regional card: why and how authoritarian gravity centres exploit regional organisations - Kneuer, Marianne; Demmelhuber, Thomas; Peresson, Raphael; Zumbrägel, Tobias (Third world quarterly, 2019)
The evidence of regional authoritarian clustering across different world regions goes together with the finding that after the end of the bipolar world regional patterns of interaction became more important. Especially in the 2000s a process of revitalisation of regional organisations and even the creation of new regional organisations took place. Interestingly, these newly founded organisations consist predominantly of authoritarian regimes. Due to the emergence and resilience of authoritarianism in the world, the question arises: To what extent do regional organisations (ROs) play a role in this phenomenon? We argue that authoritarian protagonists which we call authoritarian gravity centres (AGCs) constitute a force of attraction for countries in geopolitical proximity - and use ROs as a transmission belt and a learning room for disseminating autocratic elements. In a cross-regional comparison, based on extensive field work, we provide empirical analysis on two AGCs (Saudi Arabia and Venezuela) within their respective ROs Gulf Cooperation Council (GCC), Bolivarian Alliance for the Peoples of Our America (ALBA-TCP) and tackle the questions of why and how autocracies decide to move forward multilaterally within the RO.
Gesehen am 02.05.2025
Online veröffentlicht: 4. Juni 2018